2020
DOI: 10.1097/mao.0000000000002752
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in Diagnosis of Magnet Dislocation of Cochlear Implants: A Retrospective Study in Patients With Surgical Magnet Repositioning and Preinterventional Ultrasound Examination

Abstract: Objective: To investigate whether ultrasound is a reliable diagnostic tool to identify magnet dislocation in patients with cochlear implant. Design: Retrospective analysis. Setting: A tertiary referral medical center. Patients: Patients with cochlear implant who presented with the suspicion of magnet dislocation between January 1, 2009 and July 31, 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…28 Recently, the diagnostic ultrasound has been utilized as one of the diagnostic tools for identifying magnet dislocation. 29 Once the diagnosis of magnet dislocation has been proven, most cases would require surgical repositioning or replacement of the magnet. A literature search revealed that the procedure can be conducted under general anesthesia or local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Recently, the diagnostic ultrasound has been utilized as one of the diagnostic tools for identifying magnet dislocation. 29 Once the diagnosis of magnet dislocation has been proven, most cases would require surgical repositioning or replacement of the magnet. A literature search revealed that the procedure can be conducted under general anesthesia or local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Recently, the diagnostic ultrasound has been utilized as one of the diagnostic tools for identifying magnet dislocation. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Even in the latest CIs that are MRI-compatible, the magnet of the RS and the implant itself produce an artifact that impedes the proper assessment of the implant area [27]. In this regard, transcutaneous ultrasound is a valuable imaging modality that avoids radiation exposure and has been described for the diagnostic workup of haematoma around the CI and for detecting magnet dislocation [16][17][18]. However, the literature on the feasibility and reliability of ultrasound in other CI complications has so far been limited to a few case reports [13,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…This imaging modality has been described in the diagnosis of Robin Rupp and Vivian Thimsen contributed equally to the study. haematoma around the CI and dislocation of the internal CI magnet [16][17][18]. However, data on the use of ultrasound in other complications are rare and consist of case reports only [13,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, for people with thick scalps, or in cases of suspected mild displacement, an oblique plain film x-ray, or use of ultrasound may be used to clarify magnet seating (Fig. 3) (8,11). It is worth noting that some devices with removeable magnets are subject to silicone magnet housing fatigue and small tears that may occur during past magnet removal, which heightens risk of future magnet displacement.…”
Section: Methodsmentioning
confidence: 99%